PENGARUH MARKETING MIX TERHADAP KEPUTUSAN NASABAH UNTUK MENABUNG SIMPEDES DI PT. BANK RAKYAT INDONESIA (PERSERO) Tbk UNIT BATANG KAPAS CABANG PAINAN - Gusnawati, Reni; Yolanda Utami, Hayu; Kemala Sari, Mereta (Pendidikan Ekonomi, 2014)
ABSTRACTThis study was conducted to determine the effect of services Marketing Mix Decision Against Customer For Saving Simpedes PT . BRI (Persero) Tbk Branch Painan Cotton Trunk UnitThe population in this study are all customers who save Simpedes in PT. BRI (Persero) Tbk Branch Painan Cotton Trunk Unit, with a sample of 100 respondents. The sampling technique used is porposive Sampling. The type of data used are primary and secondary data. To analyze the effect of services Marketing Mix Influence Customer Decision Against For Saving Simpedes PT. BRI (Persero) Tbk Cotton Trunk Branch Unit Painan using multiple linear regression models with SPSS V.16.0 analysis tools .Based on the results of the hypothesis test is carried out partially can be seen that price, promotion, and process, does not have a positive and significant impact on customer decisions to save Simpedes in PT. BRI (Perser ) Tbk Branch Painan Cotton Trunk Unit. Meanwhile, product, location, people and physical evidence has a positive and significant effect on the customers decision to save Simpedes in PT. BRI (Persero) Tbk Branch Painan Cotton Trunk Unit. Then simultaneously Product, Price, Location, Promotion, People (People), Process, and Physical Evidence has a positive and significant impact on customer decisions to save Simpedes in PT . BRI (Persero) Tbk Branch Unit Cotton Trunk Painan